2021
DOI: 10.1149/1945-7111/ac2d3c
|View full text |Cite
|
Sign up to set email alerts
|

Nafion Protective Membrane Enables Using Ruthenium Oxide Electrodes for pH Measurement in Milk

Abstract: The application of conventional glass electrodes for pH measurement in food samples has a serious drawback: glass is fragile and should be handled with care in order to prevent breaking and thus contaminating the food with dangerous shattered fragments. The implementation of all-solid-state sensors allows for pH measurements without this contamination risk but their application in food samples is scarce due to their inability to be used in complex food matrices that contain fats, proteins, yeasts, etc. We can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…The TiN + Nafion pH sensor was examined by looping pH from 2 to 12, as shown in Figure 2 a. The developed sensor shows Nernstian sensitivity (−56.6 mV/pH) and a reaction time of less than 30 s, which is consistent with previous reports of pH sensors employing this type of working electrode [ 14 , 15 ]. As seen in Figure 2 b, the pH response is linear (R 2 = 0.9999) and reproducible, as summarized in Table 2 .…”
Section: Results and Analysissupporting
confidence: 86%
See 3 more Smart Citations
“…The TiN + Nafion pH sensor was examined by looping pH from 2 to 12, as shown in Figure 2 a. The developed sensor shows Nernstian sensitivity (−56.6 mV/pH) and a reaction time of less than 30 s, which is consistent with previous reports of pH sensors employing this type of working electrode [ 14 , 15 ]. As seen in Figure 2 b, the pH response is linear (R 2 = 0.9999) and reproducible, as summarized in Table 2 .…”
Section: Results and Analysissupporting
confidence: 86%
“…The specific construction of the TiN + Nafion sensor reported here has resulted in several advantages compared to the solid-state electrodes previously reported [ 14 ]. The biggest advantage is that almost all the sputtered material is used, hence, there is no wastage, and this also allows for uniform production of bulk number of electrodes.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Manjakkal et al [ 36 ] have reported another way to eliminate redox interference by placing a thin (76 nm) Ta 2 O 5 layer on the sensitive electrode of the IrO 2 pH sensor. Pre-concentrating target analytes and minimizing interference from anionic species have both been accomplished using Nafion membranes [ 37 , 38 , 39 , 40 ]. The membrane adheres well to most electrode surfaces and can prevent fouling and surface deterioration [ 41 ].…”
Section: Introductionmentioning
confidence: 99%